Global Knowledge Dynamics in Liver Cancer Nutrition: A Bibliometric Analysis with Implications for Health Education and Policy - You, Chuan; et al. (European Journal of Social Science Education and Research, 2026)
Liver cancer remains a major global health challenge and is currently one of the leading causes of cancer-related mortality worldwide. Nutrition plays a critical role across the continuum of liver cancer prevention, disease progression, treatment tolerance, and survival outcomes. Despite the growing number of studies in this area, the overall knowledge structure, research hotspots, and developmental trajectory of nutrition-related liver cancer research have not been systematically mapped. This study therefore conducted a bibliometric analysis to evaluate global research trends, collaborative patterns, and emerging themes in the field, while also considering implications for health education and policy. On 21 November 2025, publications related to nutrition and liver cancer were retrieved from the Scopus database using a structured search strategy. Only articles were included. After duplicate removal and manual screening based on titles and abstracts, 539 articles were retained for final analysis. Bibliometric mapping and visualization were performed using VOSviewer (version 1.6.20) and CiteSpace (version 6.4.R1). The analysis examined annual publication output, countries and institutions, keyword co-occurrence, clustering patterns, and citation burst trends. The results showed that 2,873 authors from 1,089 institutions across 88 countries and regions contributed to this field. China, the United States, and Japan were the most productive countries. Publication output remained limited before 2010 but increased markedly thereafter, indicating a rapid expansion of scholarly interest in the nutritional dimensions of liver cancer. Keyword analysis revealed that major research themes include prognosis, liver cirrhosis, risk factors, nutritional assessment, and nutritional status. Burst detection further showed a clear evolution in research emphasis, moving from early topics such as parenteral nutrition and liver function toward more recent interests in imaging technologies, inflammatory and immune-related indicators, prognostic nutritional index, and survival outcomes. Overall, this study provides a comprehensive overview of the global knowledge dynamics in liver cancer nutrition research. The findings may support future interdisciplinary research, improve the translation of nutritional evidence into clinical and public health practice, and inform health education strategies and policy development aimed at reducing disparities in liver cancer outcomes.